Estimating Antioxidant and Free Radical Scavenging Activity of Arbutus Pavarii Extracts - Fatma Hebail; Khayriya Rahouma; Amal Muftah; Aisha Aldroujee; Sana Elghmasi (AlQalam Journal of Medical and Applied Sciences, 2024)
The primary aim of the current study was to evaluate and compare antioxidant activity in leaves and flowers extracts of arbutus pavarii. For the purpose, the antioxidant potential of crude methanol extracts of arbutus pavarii was screened in vitro using reducing power, phosphor molybdenum assay, and radical scavenging activity by employing DPPH, NO, .OH methods as well as ferric thiocyanate (FTC) and thiobarbituric acid (TBA) tests to confirm the antioxidant potential of these extracts. Resultantly, it was confirmed that the leaves extract (LE) has displayed higher reducing ability compared with flowers extract (FE). The maximum antioxidant activity was found it in leaves methanol extract (199.38±12.73 mg of ascorbic acid/g of dry weight). The Methanolic LE was able to reduce the DPPH concentration with an IC50 of 1.09 ± mg/mL, which was noticeable stronger (P < 0.01) than that of the positive control (ascorbic acid), (IC50 = 0.01 ± 1.6 mg/mL) and FE (IC50= 1.25 ± mg/mL) as well. The LE showed slightly inhibited .OH radical (IC50, 0.78 mg/mL) compared with FE (IC50, 0.91 mg/ml). The obtained results of this investigation indicated the usefulness of utilization of arbutus pavarii leaves as a reliable source of antioxidants for nutritive and industrial purposes. هدفت هذه الدراسة إلى تقدير و مقارنة النشاطية المضادة للأكسدة في المستخلصات الكحولية لأوراق و أزهار نبات الشماري. و قد تم فحص الخاصية المضادة للأكسدة للمستخلصات الميثانولية في A. pavarii، باستخدام خاصية القدرة الاختزالية،والتقدير بالفوسفومولبدنوم ، و نشاطية كسح الجذور الحرة باستخدام طرق DPPH،NO،OH و بالمثل استخدمت اختبار اتثيوسيانات الحديديك (FTC) وحمض الثيوباربيتوريك (TBA) لتأكيد إمكانات هذه المستخلصات كمضادات للأكسدة. و اظهرت نتائج البحث بأن مستخلص الأوراق (LE) يتميز بقدرة اختزال أعلى مقارنة بمستخلص الازهار (FE). حيث تبين أعلى نشاط مضاد للأكسدة في المستخلص الميثانولي للأوراق (199.38 ± 12.73 ملجم من حامض الاسكوربيك / جم من الوزن الجاف). و تم التوصل الى نتيجة ان هذا المستخلص له القدرة على تقليل تركيز DPPH بتقديرIC50الى 1.09 ± مجم/مل، والذي كان أقوى بشكل ملحوظ (P<0.01) من المرجع الإيجابي (حمض الأسكوربيك)، (IC50 = 0.01 ± 1.6 مجم/مل) و كذلك للمستخلص الميثانولي للازهار (=IC50± 1.25ملجم/مل) و بالتوازي مع هذه النتائج فقد أظهر مستخلص الاوراق LE تثبيطًا طفيفًا لجذر OH.( IC50=0.78 مجم/مل) مقارنةً بمستخلص الازهارFE ، (0.91=IC50 مجم/مل). و بالمجمل فإن النتائج المتحصل عليها من هذه الدراسة أشارت إلى امكانية الاستفادة من أوراق نبات A. pavarii كمصدر موثوق لمضادات الأكسدة للأغراض الغذائية والصناعية